2014
DOI: 10.1007/s11655-014-1753-2
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetic activity of Piper auritum leaves in streptozotocin-induced diabetic rat, beneficial effect on advanced glycation endproduct

Abstract: The hexane extract from Piper auritum leaves can efficiently inhibit insulin resistance, AGEs formation, improvement of renal function, lipid abnormalities and oxidative stress, indicating that its therapeutic properties may be due to the interaction of hexane extract components with multiple targets involved in diabetes pathogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
(18 reference statements)
0
2
0
Order By: Relevance
“…This compound could be responsible for the antiparasitic activity of this plant [ 133 ]. On the other hand, Piper auritum has demonstrated positive effects on diabetes, cholesterol and triglycerides [ 134 , 135 ]. Moreover, the administration of P. auritum did not reduce carrageenan-induced paw edema in rats [ 136 ].…”
Section: Preclinical Studies Of Mexican Medicinal Plants Used In Inflammatory and Neuropathic Pain Treatmentmentioning
confidence: 99%
“…This compound could be responsible for the antiparasitic activity of this plant [ 133 ]. On the other hand, Piper auritum has demonstrated positive effects on diabetes, cholesterol and triglycerides [ 134 , 135 ]. Moreover, the administration of P. auritum did not reduce carrageenan-induced paw edema in rats [ 136 ].…”
Section: Preclinical Studies Of Mexican Medicinal Plants Used In Inflammatory and Neuropathic Pain Treatmentmentioning
confidence: 99%
“…Piper auritum (Piperaceae) leaves are used for treatment of diabetes in many Latin American countries . Our previous studies have shown that extracts of P. auritum inhibit the formation of AGEs. Overall, P. auritum was found to significantly inhibit protein glycation in vitro and to decrease AGE formation and glycosylated hemoglobin in diabetic rats. However, despite the fact that a number of compounds with different biological activities (mainly alkaloids) have been isolated from P. auritum , the chemical identities of the antiglycation metabolites responsible for the putative pharmacological antidiabetic activity of this plant remain to be discovered.…”
mentioning
confidence: 95%